Pengaruh Kepemimpinan Transformasional dan Kompetensi terhadap Produktivitas Pegawai melalui Motivasi Kerja sebagai Variabel Mediasi (Studi Mixed Methods Eksplanatori di Klinik Kecantikan Benings Gresik) - Emnualasari, Armita; Hidayat, Dasrun; Widjaja, Yani Restiani (Jurnal EMT KITA, 2025)
This study aims to analyze the influence of transformational leadership and human resource (HR) competencies on employee productivity, with work motivation as a mediating variable. The urgency of this research stems from the low productivity levels observed at Benings Clinic, suspected to be linked to weak leadership and inadequate HR competencies. A quantitative approach using survey methods was employed, supported by qualitative data from in-depth interviews with five key informants. Data analysis was conducted using Structural Equation Modeling (SEM) with Partial Least Squares (PLS). The results indicate that HR competencies have a significant effect on employee productivity, while transformational leadership does not have a direct or indirect influence through motivation. This finding is reinforced by qualitative data, revealing that the current leadership style lacks transformational attributes such as empowerment, inspiration, and individualized consideration. Instead, productivity improvements are primarily driven by individual capability gained through work experience and personal initiative. The study concludes that strengthening HR competencies is critical to improving productivity, while leadership roles must be reformulated to serve as a catalyst for motivation and performance. This research provides a foundation for more structured managerial interventions in the future.